Studying the Link between Organizational Learning and Employees’ Empowerment (Case Study: Qom Maskan Bank Selected Braches) - Alireza Rezaie; Ghodratollah Bagheri (International Journal of Management, Accounting and Economics, 2014)
Present study aims at investigating the relationship between organizational learning and employees’ empowerment. Organizational learning consists of such components as structure, strategy culture, and perspective based on Neefe’s theory while employees’ empowerment is considered based on introduced components by Spritz including effectiveness, significance, meritocracy, independence and trust. Present study is conducted by a descriptive survey and its population consists of management and employees in Qom Maskan Bank selected branches. In this research, 120 questionnaires were distributed by layered random sampling method and finally 100 ones were returned and analyzed. To gather data, the first questionnaire involves 12 items based on Neefe’s components while the second one (employees’ empowerment) involves Spritz indices that their validity can be supported. Chronbach’s alpha value is used to measure reliability as 0.93 and 0.94 for organizational learning and employees’ empowerment respectively. To analyze research data in SPSS and Amos software packages, such techniques as Spearman correlation coefficient, regression analysis and structural equations are used. The findings support research conceptual model and show that there is an association between organizational learning and employees’ empowerment.